Enantioselective Syntheses of Lignin Models: An Efficient Synthesis of β‐O‐4 Dimers and Trimers by Using the Evans Chiral Auxiliary. Issue 35 (26th July 2016) - Njiojob, Costyl N.; Bozell, Joseph J.; Long, Brian K.; Elder, Thomas; Key, Rebecca E.; Hartwig, William T.
Abstract: We describe an efficient five‐step, enantioselective synthesis of ( R, R )‐ and ( S, S )‐lignin dimer models possessing a β‐O‐4 linkage, by using the Evans chiral aldol reaction as a key step. Mitsunobu inversion of the ( R, R )‐ or ( S, S )‐isomers generates the corresponding ( R, S )‐ and ( S, R )‐diastereomers. We further extend this approach to the enantioselective synthesis of a lignin trimer model. These lignin models are synthesized with excellent ee (>99 %) and high overall yields. The lignin dimer models can be scaled up to provide multigram quantities that are not attainable by using previous methodologies. These lignin models will be useful in degradation studies probing the selectivity of enzymatic, microbial, and chemical processes that deconstruct lignin. Abstract : A model to break : Although lignin is optically inactive, its side chains present areas of local stereochemistry. However, sources of stereochemically defined lignin models are scarce. An efficient, five‐step enantioselective approach to lignin model dimers and trimers is described (see scheme). The process can be scaled to multigram quantities and will provide systems to study and control the reactivity of key substructural units in lignin.